Analysis of Translation Method of the Idiomatic Phrases in J.K. Rowling's Novel “Harry Potter and the Deathly Hallows” - Beatrice Stephanie; Muhammad Zaki Pahrul Hadi (Jurnal Ilmu Sosial dan Humaniora, 2024)
Among works of fiction, idiomatic phrases are some of the most complicated problems in translation. Idioms are a significant part of every language whose metaphorical meanings cannot be directly conveyed through translation. The idioms help maintain most of the subtlety and unique cultural characteristics that define a language. This paper will elaborate on the translation of idiomatic phrases in the novel "Harry Potter and The Deathly Hallows" by J. K. Rowling by reflecting upon various methods that the translator may employ while rendering English idioms into Indonesian. The data for this research was obtained through a descriptive qualitative approach, where this research was conducted on how translators retain or alter the meaning of idiomatic expressions from the novel in question in the target cultural context. The research determined that translators use literal translation, idiomatic translation, and paraphrasing, among the other techniques, which best allow them to be as faithful as possible to the original meaning and fit into the culture they are targeted for. The present study calls attention to the problems idiomatic translation poses and the role of culture in literary translation.